Multidimensional Helical Nanostructures in Multiscale Nanochannels - Lee, Sunhee (Langmuir : the ACS journal of surfaces and colloids, 2015)
We have investigated the various morphological changes of helical nanofilament (HNF; B4) phases in multiscale nanochannels made of porous anodic aluminum oxide (AAO) film. Single or multihelical structures could be manipulated depending on the AAO pore size and the higher-temperature phase of each molecule. Furthermore, the nanostructures of HNFs affected by the chemical affinity between the molecule and surface were drastically controlled in surface-modified nanochannels. These well-controlled hierarchical helical structures that have multidimensions can be a promising tool for the manipulation of chiral pores or the nonlinear optical applications